Case Report: Successful treatment of metastatic retinoblastoma with CNS involvement with anti-GD2 immunotherapy, intrathecal topotecan and reduced systemic chemotherapy - Larrosa, Cristina; Simao-Rafael, Margarida; Salvador, Noelia; Muñoz, Juan Pablo; Lavarino, Cinzia; Chantada, Guillermo; Mora, Jaume (Frontiers in Pediatrics, 2025)
High-dose chemotherapy with autologous stem cell rescue has improved outcomes in patients with metastatic retinoblastoma (RB). Despite significant advances, acute and long-term side-effects, particularly in visually impaired and cancer-predisposed patients, underscore the need for additional treatment options. Monoclonal antibodies (mAbs) directed against the tumor-associated antigen GD2 are of considerable interest. Additional lines of RB research include tracking minimal disseminated disease (MDD) to permit timely intervention in patients with CNS metastasis. We present two cases of bilateral, metastatic RB, managed with the anti-GD2 mAb naxitamab following reduced intensity myeloablative chemotherapy and autologous stem cell transplant (ASCT) with intrathecal topotecan for MDD detected in the CSF. The patients remain disease-free 10 and 9 years after initial diagnosis. While additional studies are needed, the results suggest anti-GD2 mAbs and CNS-directed chemotherapy may improve long-term outcomes and reduce cytotoxicity for high-risk patients with RB.